Experimental Support for the Possibility of Retrograde Genesis of Intraductal Carcinoma of the Prostate. (April 2023) - Kryvenko, Oleksandr N.; Punnen, Sanoj; Udayakumar, Thirupandiyur S.; Gaston, Sandra M.; Tao, Wensi; Ma, Wendi; Stoyanova, Radka; Pollack, Alan
Background. Historically, intraductal carcinoma of the prostate (IDC-P) was postulated to be a retrograde spread of high-grade invasive prostate cancer. There is evidence that IDC-P can primarily originate in the prostatic ducts. The retrograde genesis has never been experimentally or clinically confirmed before. Methods. Biopsy proven intermediate or high-risk prostate cancer was orthotopically grafted in the prostate of severe combined immunodeficiency gamma mice. Cancer growth was monitored by serum PSA levels. The animals were sacrificed and grafted areas were histological examined. Results. Twenty-one of 23 mice survived and demonstrated rising serum PSA. In 10 of 21 animals, human prostate cancer was identified orthotopically. Except for one case where the human biopsy showed a Grade Group 2 prostate cancer and mouse graft was Grade Group 5, other 9 specimens showed comparable grades. One of the specimens demonstrated a cribriform invasive prostate cancer and adjacent IDC-P. Conclusion. These experimental data offer some evidence that invasive prostate cancer can demonstrate a retrograde spread in the prostatic ducts as IDC-P. Its ability to primarily arise in the ducts has been demonstrated in other studies. However, the issue which remains unresolved is in its most common presentation of IDC-P intermixed with high-grade invasive cancer if it is the former or the latter which came first. Possibly resolving this dilemma will shed some light on the existing controversies if IDC-P should or should not be graded when invasive cancer is present.